2014
DOI: 10.1016/j.bandc.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional and longitudinal analysis of reward-related brain activation: Effects of age, pubertal stage, and reward sensitivity

Abstract: Neurobiological models suggest that adolescents are driven by an overactive ventral striatum (VS) response to rewards that may lead to an adolescent increase in risk-taking behavior. However, empirical studies showed mixed findings of adolescents' brain response to rewards. In this study, we aimed to elucidate the relationship between reward-related brain activation and risky decision-making. In addition, we examined effects of age, puberty, and individuals' reward sensitivity. We collected two datasets: Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
105
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(116 citation statements)
references
References 62 publications
(87 reference statements)
9
105
1
1
Order By: Relevance
“…These authors argue that defining adolescence as stages of development and recognizing individual differences in timing of transitions between these stages, is a much more fruitful way of understanding adolescence. There is some progress in the neuroscience literature in terms of defining biological maturity, with a focus on pubertal development in several recent studies (Braams et al, 2015;Op de Macks et al, 2011;Peper and Dahl, 2013;van Duijvenvoorde et al, 2014), which we also highlighted in the current review, but there is no emphasis yet on defining social maturity. Thus, this is a level of analysis where neuroscience can benefit from developmental approaches.…”
Section: Strengths and Weaknesses Of Neuroscience Researchmentioning
confidence: 93%
See 1 more Smart Citation
“…These authors argue that defining adolescence as stages of development and recognizing individual differences in timing of transitions between these stages, is a much more fruitful way of understanding adolescence. There is some progress in the neuroscience literature in terms of defining biological maturity, with a focus on pubertal development in several recent studies (Braams et al, 2015;Op de Macks et al, 2011;Peper and Dahl, 2013;van Duijvenvoorde et al, 2014), which we also highlighted in the current review, but there is no emphasis yet on defining social maturity. Thus, this is a level of analysis where neuroscience can benefit from developmental approaches.…”
Section: Strengths and Weaknesses Of Neuroscience Researchmentioning
confidence: 93%
“…responses to rewards(Braams et al, 2015; see alsovan Duijvenvoorde et al, 2014;Op de Macks et al, 2011). Another two-year longitudinal study observed an increase and peak in reward sensitivity in late adolescence (as indicated by BAS reward-responsiveness).…”
mentioning
confidence: 99%
“…Reward reactivity is typically measured by comparing gain to loss outcomes or to baseline and in tasks that do not include magnitude manipulations (Ernst et al ., 2005; van Leijenhorst et al ., 2010; Op de Macks et al ., 2011; van Duijvenvoorde et al ., 2014) or collapse analyses across levels of value magnitude (van Leijenhorst et al ., 2006; Braams et al ., 2015). As a result, the developmental trajectory of outcome magnitude tracking remains largely unexplored.…”
mentioning
confidence: 99%
“…Specifically, when looking at go trials that follow increasing FA errors, adolescents show increased neural tracking in the mPFC, a region previously implicated in the integration of explicit feedback (van Duijvenvoorde et al, 2014; McCormick & Telzer, 2017b). This novel finding suggests that some of the same neural systems that support integration of explicit feedback (van Noordt & Segalowitz, 2012; van Duijvenvoorde et al, 2008; McCormick & Telzer, 2017b) are similarly involved in learning from self-generated, implicit feedback information.…”
Section: Discussionmentioning
confidence: 99%
“…First, previous findings on feedback learning have involved explicit feedback (van Duijvenvoorde et al, 2014; McCormick & Telzer, 2017b), while the current study relied on internally-generated feedback in response to error commission. Additionally, these previous findings have been in the context of risk-taking behavior and rewards, while the current study relies on a difficult behavioral inhibition task.…”
Section: Discussionmentioning
confidence: 99%